Are larger and more complex port more productive? An analysis of Spanish port authorities. (March 2019) - Tovar, Beatriz; Wall, Alan
Highlights: Spanish port authorities are classified into two groups based on size and complexity. A metafrontier calculated by DEA is used to decompose productivity growth. The differences in productivity change are explained using a dynamic panel regression. Larger and more complex ports are found to have a technological advantage. Specialisation in solids, container cargo and general bulk increased productivity growth. Abstract: Several Spanish ports have grown substantially in recent decades. Ports in Spain are heterogeneous in that they differ substantially in terms of complexity, size and traffic mix. We measure the productivity of Spanish port authorities and identify the drivers of productivity taking into account this heterogeneity in order to provide more meaningful estimates of efficiency and productivity change. Using a sample of 26 ports observed over the period 1993–2016, we classify these ports into two different groups according to their overall size and their importance in terms of individual outputs. Segregating the sample into these two distinct groups permits us to draw a more precise picture of the consequences for productivity of the changes that have occurred in the sector in Spain over the last quarter of a century. Using Data Envelopment Analysis techniques, we calculate and decompose Malmquist productivity indexes using a metafrontier analysis. We use these indexes to estimate an Arellano-Bond Generalised Method Moments model to explain the differences in productivity change. Our results show that the group of large and complex port authorities had a considerable technological advantage, being closer to the metafrontier on average than the other group. Relative size, which can be interpreted as a measure of complexity of the port authority, has a strong positive influence on productivity growth. Specialisation in solids, container cargo and general bulk also increased productivity growth, but specialisation in liquids has no effect.